Translator’s Strategy in Preserving the Truth in “Lukisan wanita 1938” by Toeti Heraty Translated into English - Dian Windriani; Hajjah Zulianti (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2023)
This study examines the use of formal and dynamic equivalence as the translator’s strategy in preserving the truth in the “Lukisan wanita 1938” by Toeti Heraty translated into English. This study focuses on comparing the pattern, syntax, and meaning of two verses of poetry “Lukisan Wanita 1938” by Toeti Heraty and “Picture of A Woman 1938” (English version) translated by Iem Brown and Joan Davis. By comparing the pattern, syntax, and meaning of two verses of poetry “Lukisan Wanita 1938” by Toeti Heraty and “Picture of A Woman 1938” (English version) translated by Iem Brown and Joan Davis, it can be concluded that the translators use three strategies in translating the poem into English which are literal, rhymed, blank/free verse translation, and those strategies are categorized as formal equivalence.